If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3(1 + -1x) = -17 3x + (1 * 3 + -1x * 3) = -17 3x + (3 + -3x) = -17 Reorder the terms: 3 + 3x + -3x = -17 Combine like terms: 3x + -3x = 0 3 + 0 = -17 3 = -17 Solving 3 = -17 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x-2=5x-2 | | 84=6(m+7) | | (2x-1)+3(3x-5)=-2(2x+1) | | 10y+7=17 | | -x=-2x-1 | | 4q-3q+2q-1=11 | | 6x=2x+105 | | 0.5p+4.1=5.7-0.3p | | F=-2575+35x | | 4x-3=-5x-21 | | 30=2t-17t | | j+2=14 | | 15c=5 | | 2x+105=6x | | N+2n=57 | | -X+3(3)=12 | | -5x+10=-14-x | | 356b+56=-832 | | -17s+13s-8=-12 | | 2y-2y+y=17 | | 3x+1.5=6 | | 54=m(m-3) | | 8j(4k)= | | 15(x)=6+14(x) | | 2(x+2)=-6 | | -832=56b+356 | | 224=(W-8)+W+(W-8)+W | | -2(n-7)=-6 | | 16m-7m=18 | | 128=(W-8)+W+(W-8)+W | | 12q-7q=20 | | 3x^2+10=110+x^2 |